El símbolo de la palla en la fiesta ritual del Corpus Christi en la parroquia de la Merced y su relación con el Sumak Kawsay - Estrella Rivadeneira, María Manuela (2014)
As a search for answers to building a just society between human beings and nature, has raised the concept of Sumak Kawsay as a guideline to follow in the Constitution of Ecuador, a result of social struggles of various social sectors Ecuadorian society. An understanding of this concept arises from a metaphor full of art and resistance: the Andean religious festival, which brings ancient symbols meanings that reveal a worldview manifest. Through an ethnography of Palla symbol is discussed in the ritual feast of Corpus Christi, in the Alangasí, La Merced; which is the Pachamama conception, which is the building Sumak Kawsay. Important aspects of the culture of the investigated area are evident and valuable content Skyline also clarify under construction Sumak Kawsay